Monoamine Oxidase B Expression Correlates with a Poor Prognosis in Colorectal Cancer Patients and Is Significantly Associated with Epithelial-to-Mesenchymal Transition-Related Gene Signatures - Yang, Yi-Chieh; Chien, Ming-Hsien; Lai, Tsung-Ching; Su, Chia-Yi; Jan, Yi-Hua; Hsiao, Michael; Chen, Chi-Long (International journal of molecular sciences, 2020)
Monoamine oxidases (MAOs) including MAOA and MAOB are enzymes located on the outer membranes of mitochondria, which are responsible for catalyzing monoamine oxidation. Recently, increased level of MAOs were shown in several cancer types. However, possible roles of MAOs have not yet been elucidated in the progression and prognosis of colorectal carcinoma (CRC). We therefore analyzed the importance of MAOs in CRC by an in silico analysis and tissue microarrays. Several independent cohorts indicated that high expression of MAOB, but not MAOA, was correlated with a worse disease stage and poorer survival. In total, 203 colorectal adenocarcinoma cases underwent immunohistochemical staining of MAOs, and associations with clinicopathological parameters and patient outcomes were evaluated. We found that MAOB is highly expressed in CRC tissues compared to normal colorectal tissues, and its expression was significantly correlated with a higher recurrence rate and a poor prognosis. Moreover, according to the univariate and multivariate analyses, we found that MAOB could be an independent prognostic factor for overall survival and disease-free survival, and its prognostic value was better than T and N stage. Furthermore, significant positive and negative correlations of MAOB with mesenchymal-type and epithelial-type gene expressions were observed in CRC tissues. According to the highlighted characteristics of MAOB in CRC, MAOB can be used as a novel indicator to predict the progression and prognosis of CRC patients.